Use of intravenous immunoglobulin for the treatment of autoimmune encephalitis: audit of the NHS experience. Issue 9 (September 2018) - Kinsella, JA; Irani, SR; Hollingsworth, R; O'Shaughnessy, D; Kane, P; Foster, M; Schott, JM; Lunn, MP
Objectives: The treatments of limbic and other autoimmune encephalitis include immunosuppression, symptomatic treatment, and in the case of paraneoplastic syndromes, appropriate therapy for underlying neoplasms. When immunotherapy is considered, intravenous immunoglobulin is one option for treatment, either alone or in combination with corticosteroids. To date, however, evidence for the use of intravenous immunoglobulin in this context comes from case series/expert reviews as no controlled trials have been performed. We aimed to analyse the NHS England Database of intravenous immunoglobulin usage, which was designed to log use and guide procurement, to explore usage and therapeutic effect of intravenous immunoglobulin in autoimmune encephalitis in England. Design: We conducted a retrospective audit and review of the NHS England Database on intravenous immunoglobulin use. Setting: NHS England Database of intravenous immunoglobulin use which covers secondary and tertiary care prescribing and use of intravenous immunoglobulin for all patients in hospitals in England. Participants: Hospital in-patients with confirmed or suspected autoimmune/limbic encephalitis between September 2010 and January 2017. Results: A total of 625 patients who were 18 years of age or older were treated with intravenous immunoglobulin for autoimmune encephalitis, of whom 398 were determined as having 'highly likely' or 'definite' autoimmune/limbic encephalitis. Ninety-six percent were treated with a single course of intravenous immunoglobulin. The availability and accuracy of reporting of outcomes was very poor, with complete data only available in 27% of all cases. Conclusions: This is the first review of data from this unique national database. Whilst there was evidence for clinical improvement in many cases of patients treated with intravenous immunoglobulin, the quality of outcome data was generally inadequate. Methods to improve quality, accuracy and completeness of reporting are crucial to maximise the potential value of this resource as an auditing tool.